Beyond risk: understanding a framework for improving adolescents’ sexual health in Nigeria - Oluwaseyi, Somefun Dolapo (My University, 2019)
The determinants of risky sexual behaviours among youth have been widely debated in epidemiology, public health, demography and in other social sciences. A number of scholars such as Kabiru, Izugbara, and Beguy (2013); Okigbo, Kabiru, Mumah, Mojola, and Beguy (2015) and (Odimegwu & Somefun, 2017) argue that risky sexual behaviours among youth are influenced by risk factors at both individual and community levels. However, fewer studies have explored the prevalence and patterns of protective behaviours among youth nor have they adequately addressed the factors that contribute to protective sexual behaviours in the lives of adolescents. The question “Why do some youth engage in protective sexual behaviours in the same social environment while others who do not?” remains unanswered. The purpose of this study is to understand protective sexual behaviours of young people aged 15-24 in Nigeria and the risk and protective factors associated with those behaviours. By protective sexual behaviours, I mean those behaviours that protect an individual from risk related to sexual activities. The behaviours considered in this study were; primary and recent abstinence, single sexual partnerships, condom use at last sex and HIV testing. The study was placed within the broad ecological framework and the risk and resilience framework in order to understand why youth engage in protective sexual behaviours in unfavourable environments and examine what can be learnt from these youth. The ecological framework argues that factors that affect protective sexual behaviours of young people interact at different levels – individual, family, community and society. The risk and resilience framework is based on evidence that both risk and protective factors could interact with in the life of an individual to result in protective outcomes. Specifically, I used a concurrent triangulation approach to examine the influence of protective and risk factors on protective sexual behaviours among youth in Nigeria, and to understand why some youth engage in protective behaviours in the face of extreme vulnerability; where extreme vulnerability could be within intimate relationships, at parties or social gatherings and being alone with a friend. I used three rounds of the Nigerian Demographic and Health Survey (2003, 2008 and 2013) to examine the patterns of protective sexual behaviours among youth aged 15-24 in Nigeria. The NDHS results from the quantitative analysis informed the purposive sampling of four study sites (Edo, Enugu, Kano and Osun State) representative of the three major ethnic groups and a control site in Nigeria where youth were sampled randomly for data collection. Focus groups (16 per state) and in-depth interviews (10 per state) stratified by place of residence and gender were used to develop themes concerned with resilience among youth. This resulted to a total of 64 FGD’s and 80 IDIs. The third phase involved generating a questionnaire to deal with themes that could not be measured with the national dataset with a sample of 2, 339 youth in the four states. Results from the DHS showed that the percentage of males delaying sex as at age15 increased from 57% in 2003 to 66% in 2013 but a slight increase was evident for females (32% vs 36%). This increase in abstinence was similar to increase in condom use at last sex and HIV testing among youth with evident gender differentials. Findings from the FGD’s and IDIs revealed that fear of early fatherhood, pregnancy, experience of coerced sex and parental monitoring were individual and familial factors associated with protective sexual behaviours among youth. At the community level, accessibility to youth friendly services and presence of role models were some other factors that enabled youth to engage in protective sexual behaviours. This study contributed to the rarely acknowledged issue of youth protective sexual behaviours using mixed methods in African social demography in the Nigerian context. The study has shown that there are Nigerian youth engaging in protective sexual behaviours contrary to the majority of available literature that has consistently pained youth in the negative way. This implies that continuous examination of protective sexual behaviours among youth has tremendous potential to promote not health youth sexual and reproductive health.
The thesis submitted in fulfillment for the requirements of Doctor of Philosophy in Demography and Population Studies to the Schools of Public Health and Social Sciences of the University of the Witwatersrand, Johannesburg, 2019